Politics of Rereading the Contemporary World through Myth in Dorris Lessing’s The Cleft - Phuyal, Komal Prasad; Basnet, Rojina (NPRC Journal of Multidisciplinary Research, 2025)
Background: Dorris Lessing (1919-2013) critiques conventional historical narratives in her novel The Cleft (2007). The novel interrogates the contemporary imbalance of power by examining prevailing gender relations and the narrative of human evolution.Method: This study adopts a new historicist framework, drawing on the work of French philosopher Michel Foucault (1926-1984), who critically examines the relationship between power structures and established narratives.Result: Lessing suggests a political objective in writing this contemporary history, aiming to demonstrate that the official version is merely one among many possible explanations of history.Conclusion: Through a Foucauldian analysis of Lessing’s novel, it becomes evident that her political aim is to challenge conservative interpretations of political order by illuminating alternative explanations of women’s evolution in society.Novelty: This study adds a new dimension to the study of reading fiction by exploring its social history. Lessing’s creative intervention serves as a tool to decenter the prevailing discourse and push forward an alternative way of understanding the social reality.